THE LITERARY SOURCES OF THE “LAYLI AND MAJNUN” NARRATIVE POEMS - Turdiyeva Maftuna Abdurahmonovna (International Journal of Literature and Language Studies, 2026)
In Eastern literature, in particular, in epic poetry, the development of the theme of Layla and Majnun and its inherent guiding principles were manifested in the epics “Layla and Majnun”, created within the framework of the tradition of khamsanavisi. It is necessary to recognize that literary sources were important factor in the emergence of the tradition of writing works on this topic. The article analyzes information on the genesis of the images of Layla and Majnun based on the source of the poet scholar Abul Faraj Isfahani.